2014
DOI: 10.1159/000363416
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructing Middle Hepatic Vein Tributaries in Right-Lobe Living Donor Liver Transplantation

Abstract: Aims: To investigate the effectiveness of our technique and policy in reconstructing middle hepatic vein (MHV) tributaries of patients undergoing right-lobe living donor liver transplantation (LDLT). Methods: From January 2001 to December 2010, 186 adult patients underwent right-lobe LDLT without the MHV. Patients were divided into two groups: group A (n = 71) and group B (n = 115) without or with the MHV tributaries reconstruction. We evaluated the serum liver function markers after transplantation and monito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 47 publications
0
3
1
Order By: Relevance
“…The patency of the hepatic vein tributaries, however, was suboptimal. Previous reports, including ours, have indicated a high incidence of occlusion of the MHV tributaries, V5 and V8, over the longterm period . In contrast, the present study revealed a significantly better patency rate of the IRHV compared with V5 and V8.…”
Section: Discussioncontrasting
confidence: 79%
“…The patency of the hepatic vein tributaries, however, was suboptimal. Previous reports, including ours, have indicated a high incidence of occlusion of the MHV tributaries, V5 and V8, over the longterm period . In contrast, the present study revealed a significantly better patency rate of the IRHV compared with V5 and V8.…”
Section: Discussioncontrasting
confidence: 79%
“…Preoperative US of the GSV was adopted to determine whether autologous vein grafts could be used for vascular reconstruction. The most important advantage of an autologous graft over an artificial one is better biocompatibility, which greatly reduces the risk of graft rejection while reducing the postoperative anticoagulant therapy, thus reducing the possibility of postoperative bleeding 40, 41. In addition, the GSVs are easy to harvest, and their removal does not cause many adverse effects; all the preceding reasons make the GSV the ideal material for vascular reconstruction 26, 32, 35…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the ratio of RLV to ing. 40,41 In addition, the GSVs are easy to harvest, and their removal does not cause many adverse effects; all the preceding reasons make the GSV the ideal material for vascular reconstruction. 26,32,35 The management of the anhepatic phase is another key issue for maintaining an uneventful intraoperative course.…”
Section: Discussionmentioning
confidence: 99%
“…The homologous vein can be from the same donor besides liver graft (internal jugular vein, ovarian, or inferior mesenteric vein), cryopreserved vessels from group‐matched deceased donor (eg, iliac vessels), or another recipient portal vein. Synthetic vascular grafts can be ePTFE or Dacron …”
Section: Discussionmentioning
confidence: 99%